Accuracy assessment of MODIS active fire products in southern African savannah woodlands. (23rd November 2017) - Masocha, Mhosisi; Dube, Timothy; Mpofu, Ndumezulu T.; Chimunhu, Silvester
Abstract: Satellite remote sensing offers a cost‐effective method for monitoring fire occurrence in savannah systems, for proper fire management. However, the ability of satellite fire products to detect active fire is known to vary depending on the terrestrial ecosystems and sensor characteristics. In this study, the overall accuracy, kappa coefficient of agreement and true skill statistic (TSS) were used to assess the accuracy of two MODIS fire products (MOD14A1 and MCD14ML) to detect active fire at two savannah woodland sites dominated by Baikiaea plurijuga and Brachystegia spiciformis in Zimbabwe. In both sites, MOD14A1 with a coarse spatial resolution of 1 km had a poor index of agreement with ground fire data (kappa = 0, TSS = 0 and overall accuracy ≤ 0.4). By contrast, a moderate to strong agreement between MCD14ML and active fires measured on the ground was observed at both study sites (overall accuracy ≥ 0.7, kappa ≥ 0.6 and TSS ≥ 0.6; Table 1 ). It was therefore concluded that MCD14ML, with a spatial resolution of 375 m, is a more suitable product for detecting active fires in both Baikiaea plurijuga and Brachystegia ‐dominated savannah woodlands of southern Africa compared to MOD14A1.